Effect of isolated Vitamin D supplementation on the rate of falls and postural balance in postmenopausal women fallers: A randomized, double-blind, placebo-controlled trial - Cangussu, Luciana Mendes [UNESP]; Nahas-Neto, Jorge [UNESP]; Orsatti, Claudio Lera [UNESP]; Poloni, Priscila Ferreira [UNESP]; Schmitt, Eneida Boteon [UNESP]; Almeida-Filho, Benedito [UNESP]; Nahas, Eliana Aguiar Petri [UNESP] (Wolters Kluwer, 2016)
Objective: To evaluate the effect of isolated vitamin D supplementation (VITD) on the rate of falls and postural balance in postmenopausal women fallers. Methods: In this double-blind, placebo-controlled trial, 160 Brazilian younger postmenopausal women were randomized into two groups: VITD group, vitamin D3 supplementation 1,000 IU/day/orally (n = 80) and placebo group (n=80). Women with amenorrhea at least 12 months, age 50 to 65 years, and a history of falls (previous 12 months) were included. Those with neurological or musculoskeletal disorders, vestibulopathies, drugs use that could affect balance and osteoporosis were excluded. The intervention time was 9 months. Postural balance was assessed by stabilometry (computerized force platform) and investigation on the occurrence/recurrence of falls was performed by interviews. The plasma concentration of 25-hydroxyvitamin D [25(OH)D] was measured by highperformance liquid chromatography. Statistical analysis was achieved by intention-to-treat, using analysis of variance, Student's t test, Tukey test, chi-square, and logistic regression. Results: After 9 months, mean values of 25(OH)D increased from 15.0±7.5 ng/mL to 27.5±10.4 ng/mL (45.4%) in the VITD group, and decreased from 16.9±6.7 ng/mL to 13.8±6.0 ng/mL (-18.5%) in the placebo group (P<0.001). The occurrence of falls was higher in the placebo group (46.3%) with an adjusted risk of 1.95 (95% confidence interval [CI] 1.23-3.08) times more likely to fall and 2.80 (95% CI 1.43-5.50) times higher for recurrent falls compared to the VITD group (P<0.001). There was reduction in body sway by stabilometry, with lower amplitude of antero-posterior (-35.5%) and latero-lateral (-37.0%) oscillation, only in the VITD group (P<0.001). Conclusions: In Brazilian postmenopausal women fallers, isolated vitamin D supplementation for 9 months resulted in a lower incidence of falls and improvement in postural balance.
Keywords: Falls; Menopause; Postural balance; Vitamin D